PRAKTEK PROSTITUSI DAN PENGARUH TREND KUNJUNGAN WISATAWAN MANCA NEGARA DI KOTA YOGYAKARTA - Erlangga Brahmanto (Jurnal Pariwisata, 2015)
ABSTRACT          Tourism in addition to having a positive impact in the economy also has a negative impact on socialculture . The development of tourism is directed into one of the country 's foreign exchange to support development activities likely to lead to a progressive economic aspect , cultural aspect , whichpressure due to the shift in immigrant communities are less concerned about socialcultural environment . Yogyakarta is very rapid progression from year to year . prostitution in the city of Yogyakarta is also experiencing significant growth .    This is as a consequence of the results of the development of tourism in Yogyakarta . Sarkem region , Babarsari , Parangkusumo beach is a picture of the author wants to lift to the research topic entitled " Practice Prostitution and the influence of Tourist Visits in Yogyakarta” . This study addresses the two aspects , namely the economic and cultural aspects of progressive regressive . In this issue there is a dilemma from year to year , due to new entrants to the practice of sex ( prostitution ) is hidden in the Babarsari , rented houses or spread and some prostitutes is a student or students from leading universities in Yogyakarta . therefore in this study can be found three major problems are : ( a) Type prostitution which flourished in Babarsari , Sarkem , Parangkusumo Beach ( b ) Relationship Patterns between a prostitute with the local community in terms of tourism development and the preservation of cultural values , ( c ) Effect of prostitution to local culture and tourism development .         This study uses field data collection methods, methods of interviewing and observation and data collection methods literature . development of tourism in Yogyakarta  impact on the practice of Presence sex ( prostitution ) hidden in Boarding House or rent , renting , given the tourist area of Yogyakarta area wet with Rupiah . This is a new settlement , mostly inhabited by new settlers . This occurs because of the increased demands of public life . But the authors believe this problem can be solved optimistic and avoid conflict in the community , by avoiding rent or boarding house or place of business to be a veiled prostitution Keywords : Tourism , Conflict , Prostitution , Sex , Tourism Economy